Revisiting and Extending the Argument: A Rejoinder to Wiles and Lipsitz - Alan J. DeYoung (Journal of Research in Rural Education, 1995)
We'd like to thank Jon Wiles for inadvertently confirming many of the points we earlier raised about the unexamined assumptions underlying the rhetoric behind the middle school concept (DeYoung, Howley, & Theobald, 1995), points that he appears not to have fully understood. We offer a different sort of thanks to Joan Lipsitz. She reluctantly appears to agree with portions of our analysis, but also gives us room to elaborate several critical issues rather than merely reiterate our earlier discussion. Were our rejoinder a court case, we would metaphorically implicate Wiles as a defendant, while calling upon Lipsitz as a hostile witness for the prosecution.